Stuffing the nail: A simple technique for the extraction of a broken femoral nail. (June 2017) - Lovell, Jane; Krishna, Damodaran; Gehr, Eugene
Abstract: The extraction of broken femoral nails can be a challenging procedure and surgeons should be familiar with many different techniques. This paper demonstrates a case study and new, simple and cost effective technique for the removal of broken cannulated femoral nails. Our technique uses two guide wires of variable diameter and had several key points of differentiation from previous methods. Firstly, stuffing the nail with guide wires of greater total diameter than the cannula; secondly, reversing the second guide wire and finally, bending the tips of the wires. These innovations allow the technique to be used for narrow cannulated nails, superior purchase along the length of the nail, easy wire insertion and limited soft tissue damage. Our technique for the removal of broken femoral nails is quick, effective, cheap and easy to replicate and can be used by any generalist orthopaedic surgeon with basic equipment.